An Analysis of the Second-Year Student's Ability in Identifying Parts of Speech at the English Department of Fakultas Bahasa dan Seni Universitas Negeri Padang - Julia Anggraini; Nofrina Eka Putri (Journal of English Language Teaching, 2022)
This study aims to analyze the second-year students' ability in identifying parts of speech at the English Department of the Faculty of Language and Arts, Padang State University. This research is descriptive quantitative. The population in this study were all students of English Education for the 2020/2021 academic year, which consisted of five classes with a total of 137 students. The researcher took 20% of the total population using a random sampling technique with a sample of 27 students. The results of this study indicate that students are still confused about identifying parts of speech because some words can function in different parts of speech. Therefore, students' ability in identifying parts of speech is in fair category. In other words, the ability to identify parts of speech has not been maximized. Therefore, it can be seen that the average achievement of all components of a part of speech is 63.85, which can be categorized as fair.